A research agenda for helminth diseases of humans: health research and capacity building in disease-endemic countries for helminthiases control. - Mike Y Osei-Atweneboana; Sara Lustigman; Roger K Prichard; Boakye A Boatin; María-Gloria Basáñez (Public Library of Science (PLoS), 2012)
Capacity building in health research generally, and helminthiasis research particularly, is pivotal to the implementation of the research and development agenda for the control and elimination of human helminthiases that has been proposed thematically in the preceding reviews of this collection. Since helminth infections affect human populations particularly in marginalised and low-income regions of the world, they belong to the group of poverty-related infectious diseases, and their alleviation through research, policy, and practice is a sine qua non condition for the achievement of the United Nations Millennium Development Goals. Current efforts supporting research capacity building specifically for the control of helminthiases have been devised and funded, almost in their entirety, by international donor agencies, major funding bodies, and academic institutions from the developed world, contributing to the creation of (not always equitable) North-South "partnerships". There is an urgent need to shift this paradigm in disease-endemic countries (DECs) by refocusing political will, and harnessing unshakeable commitment by the countries' governments, towards health research and capacity building policies to ensure long-term investment in combating and sustaining the control and eventual elimination of infectious diseases of poverty. The Disease Reference Group on Helminth Infections (DRG4), established in 2009 by the Special Programme for Research and Training in Tropical Diseases (TDR), was given the mandate to review helminthiases research and identify research priorities and gaps. This paper discusses the challenges confronting capacity building for parasitic disease research in DECs, describes current capacity building strategies with particular reference to neglected tropical diseases and human helminthiases, and outlines recommendations to redress the balance of alliances and partnerships for health research between the developed countries of the "North" and the developing countries of the "South". We argue that investing in South-South collaborative research policies and capacity is as important as their North-South counterparts and is essential for scaled-up and improved control of helminthic diseases and ultimately for regional elimination.